Kaempferia galanga (L.): An Updated Overview of In Vitro and In Vivo Antioxidant Properties - Riastri, Anami (Journal of Food and Pharmaceutical Sciences, 2024)
Kaempferia galanga L. (K. galanga) locally called aromatic ginger or “kencur" in Bahasa is traditionally for the treatment of various diseases related to antioxidants such as anti-inflammatory, anti-cancer, and immunomodulator. This paper aims to provide a critical review of the current antioxidant activity of K. galanga using in vitro and in vivo assays. The information and data of K. galanga were collected from various resources such as Scopus, PubMed, Science Direct, and Google Scholar. The results showed that K. galanga plays a role in defense systems against oxidative stress. Several in vitro assays have been used to measure the antioxidant activity of K. galanga, namely,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reduction of antioxidant power (FRAP), 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS). Whereas, the parameter in vivo antioxidant assay of K galanga including lifespan, survival life, intracellular reactive oxygen species (ROS) level, malondialdehyde (MDA) level, and antioxidant enzyme activities: superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px). Based on the findings, it can be indicated that K. galanga has powerful antioxidant activities and, therefore could have the potential as a natural antioxidant.